(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In the article, the development of students in all aspects, raising their spiritual-moral, intellectual potential in accordance with world standards, especially science and enlightenment in ensuring the development of future highly educated specialists as well-rounded people The contents of the works of the famous philosopher Muhammad Abu Hamid Ghazali, who made a worthy contribution to civilization, was one of the great sages of the Eastern Renaissance, possessor of religious and worldly knowledge, served the development of tawhid, kalam, tafsir, and hadith science.